A Pair of Compound Heterozygous IARS2 Variants Manifesting West Syndrome and Electrolyte Disorders in a Chinese Patient - Zhou, Feiyu; Yi, Gui; Liu, Xiangyu; Sheng, Wenchao; Shu, Jianbo; Li, Dong; Cai, Chunquan (Global Medical Genetics, 2024)
Background Aminoacyl-tRNA synthetases (ARSs) are evolutionarily conserved enzymes that ensure the accuracy of the translation process. Isoleucyl-tRNA synthetase 2 (IARS2) gene is a type of ARS that encodes mitochondrial isoleucine-tRNA synthetase. Pathogenic variants in the IARS2 gene are associated with mitochondrial disease which involves several patients presenting broad clinical phenotypes. These clinical phenotypes include West syndrome, Leigh syndrome, and Cataract, growth hormone deficiency, sensory neuropathy, sensorineural hearing loss, and skeletal dysplasia syndrome. Only 29 cases have been reported worldwide. The patient manifested recurrent convulsions, and specific clinical manifestations included electrolyte disorders and recurrent infections.Methods Whole-exome sequencing was performed on the child with West syndrome. Three-dimensional structure reconstruction and thermodynamic stability prediction were performed to further analyze the relationship between variation and phenotype.Conclusion This study further expands the clinical spectrum of IARS2 pathogenic variants. The case summaries help raise clinical awareness of IARS2-associated disease and reduce misdiagnosis.Result In this report, a 13-month-old girl was diagnosed with West syndrome and Leigh syndrome for 7 months. Compound heterozygous variants in the IARS2 gene (NM_018060.4), c.2450G>A (Arg817His) and copy number variation (NC_000001. 11: g. (220267549_220284289) del), were detected by WES. This study further expands the clinical spectrum of IARS2 pathogenic variants. The case summaries help raise clinical awareness of IARS2-associated disease and reduce misdiagnosis.
Keywords: West syndrome; CAGSSS; aminoacyl-tRNA synthetases